Reforma do Ensino Médio, Projeto Pedagógico da Confederação Nacional da Indústria e a crise do Mundo do Trabalho no Brasil: delineamentos para a formação dos estudantes da classe trabalhadora - Leite, Guilherme Antunes (2021)
The main objective of this thesis was to understand the formative project of the High School Reform (HSR) approved by Law No. 13.415/2017 from the mediations of the Brazilian State and the influence and guidance of the National Confederation of Industry (CNI). The HSR in the Brazilian educational scenario integrates contextual processes that resume the foundations of the Law Project - LP 6.840/2013, archived after rejected by the National Movement for the Defense of High School and other social entities and restarted in the Provisional Measure 746/2016, in the context of the political crisis in Brazil after the President Dilma Rousseff's impeachment process. Although this measure was widely rejected by the student movement across the country, it became law in 2017, leading to the present research object of this study. With this, the intent of the research was also to: (a) understand the basis of capitalist sociability in the economic, social and political context in which the process of formulating the REM was developed from the characterization of the Brazilian labor world and its relationship to the organization and identity of High School (HS); b) understand the foundation of neoliberal educational reforms and the relationship with the bourgeois formative project mediated by the Brazilian State through educational policies, highlighting the example of the influence of the CNI for the REM formulation process; and c) unveil the political organization of the REM and the HS pedagogical project at present from Law 13. 415/2017 according to its processes, class struggle and formation intended for working-class students. To this end, we assume as a method the Historical Materialism of the Social Theory of Karl Marx and Friedrich Engels regarding the analysis of the radicality of the social reality of the contemporary capitalist mode of production, based on the categories of capital, labor, State, reproduction and social being. Methodologically, we conducted a bibliographic review and document analysis of texts, decrees, guidelines, and projects at the state level and of the studied business group: Provisional Measure 746/2016; Law 13.415/2017; as well as CNI documents. We understand educational policy as a process and seek in our analyses to investigate its elaborations and contents. Theoretically and methodologically oriented, the research problematic consisted in answering the question: What is the schooling intended and mediated by the Brazilian State from REM through the CNI's guidelines in the formulation process and content of Law 13.415/2017? What we see is that the State mediates education, that is, the pedagogical project of the bourgeoisie as required by the conditions of the capital and labor relationship in capitalism. Thus, in the Brazilian sphere, REM aligns itself to the inconsistencies and instabilities of the world of work in crisis and collapse that intends and requires a forma(ta)tion of HS students for a life project guided by the principle of the precarization of life. The 2017 law that legitimized the REM is the synthesis of the education proposal reconducted over three decades by the national business class, thus, the CNI fulfills the role of being the organized bourgeois fraction that articulates and acts as a pressure group with the State. With this, the delineations for the formation of working class students are those that make possible the consolidation of a new human capital (cosmopolitan and performative) capable of adapting and forging ways to overcome social problems - unemployment and uncertainty.